Current status of cancer education in developing and developed countries: identifying the disparities and bridging the gap - Yilihamu, Gulimire; Aierxiding, Shalayiding (Frontiers in Public Health, 2025)
Cancer constitutes a significant public health issue globally. according to the World Health Organization (WHO), cancer is the second most common cause of mortality worldwide, accounting for 10% of all deaths in 2020–2022. GLOBOCAN 2020 data from the International Agency for Research on Cancer (IARC) show that age-standardized incidence rates (ASR) in developed nations are markedly higher than those in developing countries. For instance, Australia reports an ASR of 468.0 per 100,000, while India’s ASR stands at only 97.1 per 100,000. This discrepancy can be attributed partly to more robust cancer registration systems, extensive screening programs, and cancer education prevalent in developed countries. Notably, the participation rate in breast cancer screening in the United States surpasses 70%, in contrast to less than 20% in certain African regions, as reported by the National Cancer Institute (NCI). Through a systematic review, this paper examines the gaps in cancer education policies, resource allocation, educational approaches, public awareness, and healthcare system support between developed and developing countries, proposing strategies to bridge these gaps. The research reveals that developed countries boast well-established policy support, ample financial investment, and advanced educational technologies in cancer education. In contrast, with a later start, developing countries face challenges such as resource scarcity, incomplete policies, and insufficient public awareness. To narrow these disparities, developing countries must strengthen policy support, increase financial investment, particularly in rural areas, improve cancer prevention and control legislation, enhance the accessibility and quality of cancer education, promote innovative educational methods, and elevate public awareness of cancer prevention and control.